Treatment outcomes in hepatitis C virus genotype 1a infected patients with and without baseline NS5A resistance‐associated substitutions. (30th July 2020) - Dietz, Julia; Vermehren, Johannes; Matschenz, Katrin; Buggisch, Peter; Klinker, Hartwig; Schulze zur Wiesch, Julian; Hinrichsen, Holger; Peiffer, Kai‐Henrik; Graf, Christiana; Discher, Thomas; Trauth, Janina; Schattenberg, Jörn M.; et al.
Abstract: Background & Aims: The presence of baseline resistance‐associated substitutions (RASs) reduced sustained virologic response (SVR) rates in chronic hepatitis C virus (HCV) genotype 1a infected patients treated with Elbasvir/Grazoprevir (EBR/GZR). This study aimed to evaluate the frequency of NS5A RASs and treatment outcomes in patients for whom EBR/GZR was intended. Methods: We sequenced NS5A in 832 samples from German genotype1a‐infected DAA‐naïve patients population‐based, which were collected in the European Resistance Database. Treatment outcomes and clinical parameters were evaluated in 519 of such patients retrospectively. Results: Overall, 6.5% of patients harboured EBR‐specific NS5A RASs at baseline, including Q30H/R (3.3%), L31M (1.8%), Y93H (1.6%) and other individual variants. Antiviral treatment, including EBR/GZR, was initiated in 88% of the patients. In the absence of RASs, the majority of patients received EBR/GZR for 12 weeks (57%) and the SVR rate was 97% compared to 99% SVR achieved using other DAA regimens (LDV/SOF ± RBV, G/P, PrOD + RBV, VEL/SOF). Various regimens were used in the presence of RASs and SVR rates were high following treatment with LDV/SOF (100%), G/P (83%), PrOD/RBV (100%), VEL/SOF (100%), SMV/SOF (100%) and EBR/GZR + RBV for 16 weeks (100%). However, two patients received EBR/GZR for 16 weeks without RBV and one relapsed. Conclusions: EBR/GZR treatment with or without RBV for 12 or 16 weeks according to a baseline RAS analysis was highly effective with ≥97% SVR in patients with genotype 1a. EBR/GZR without RBV should be avoided in patients with RASs. High SVR rates were also achieved using other 8‐ or 12‐week DAA regimens.